Plan de Seguridad y Salud en el Trabajo para la Empresa “Ferrocentro Unimax” de la Ciudad de Loja. - Yaguana Yaguana, Valeria Anavel (2024)
This Curricular Integration paper, entitled ‘Safety and Health at Work’s Plan for the company Ferrocentro Unimax in the city of Loja’, was designed to evaluate the safety and health conditions at work, for which a detailed diagnosis of the current situation of the company was executed in order to design the safety plan. The project was of an exploratory type with a qualitative approach, and applied a research design (action research), using the inductive method; for which, we used some techniques such as literature review, direct observation through the checklist issued by the Department of Labour, a survey applied to employees and an interview to the company manager. Based on the information obtained, areas for improvement in the company were identified, such as the lack of training, the realization of drills and a deficient check of fire and evacuation equipment signage. These findings enabled the elaboration of an Occupational Health and Safety Plan for the company Ferrocentro Unimax, aligned with the current regulations of the Department of Labour, with the aim of preventing risks and enhancing the workers’ health and safety. In addition, a budget was calculated to enable the implementation of the Plan, including the acquisition of personal protective equipment and training to reduce risks and promote a safe working environment.